Influence of weak-layer heterogeneity on snow slab avalanche release: application to the evaluation of avalanche release depths - Gaume, Johan; id_orcid:0 000-0001-8931-752X; Chambon, Guillaume; Eckert, Nicolas; Naaim, Mohamed (Journal of Glaciology, 2013)
ISSN:0022-1430 ISSN:1727-5652